(3efJgi GdWdH ef CTYGQ GdYQHs - (3GHf ejehf , eMeO Hf GdeHGQc Hf eMeO Hf ejehf,J (B589 (3g` s
(3ChdgG (B:s
"(3gPG cJGH LeYJ ajg Cda bUjOI hGNJQJgG ef CTYGQ GdYQH s
(3BNQgG (B:s
(3jfJgi HTYQ (B"(3cKjQ(B" s
(3Hg VHWs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3LeY s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs